Analysis of the Influence of Continuous Variable Characteristic Parameters on the Quality of HMCVT Transition - Yang Zhaohu; Du Youhong; Tan Yunying; Li Qingtao; Chen Xinghai (Jixie chuandong)
To analyze the stage changing quality of small and medium-sized tractors equipped with hydro-mechanical continuously variable transmission (HMCVT) in the process of power changing, based on a HMCVT with continuously variable characteristic parameters, the traditional gear planetary transmission structure was changed into the traction planetary transmission structure, and a multi-stage HMCVT system was proposed. Considering the influence of changing time and displacement ratio of the hydraulic system on the stage changing quality, AMESim modeling and simulation analysis of the multi-stage HMCVT system were carried out by adding a variable concerning which the characteristic parameters of the traction planetary array were continuously changing. When the change period t0=0.8 s was set in the simulation, multi-parameter adjustment analysis was carried out on the three evaluation indexes of the change period quality, such as velocity drop, impact degree and sliding power, in the characteristic parameter k 1.5-2. The design of the three-stage HMCVT system can reduce the maximum sliding power by 25.6% or the maximum impact degree by 20.84% by changing the value of the characteristic parameter k in the L and H stages. By changing the value of the characteristic parameter k in the S and L sections, the sliding work can be reduced by 6.68%, but the impact of changing the characteristic parameter k on the impact degree changes within 1%. The overall velocity drop will increase with the increase of the characteristic parameter k. The research results can provide reference for further improving the stage changing quality.